Properties of collagen from barramundi (Lates calcarifer) skin - Bakar, Jamilah; Mohamad Razali, Umi Hartina; Mat Hashim, Dzulkifly; Sazili, Awis Qurni (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2013)
The properties of collagens from Barramundi (Lates calcarifer) skin obtained by acid solubilized (control), pepsin and papain aided extractions were investigated. The yields of collagens (dry weight basis) for acid solubilized, pepsin and papain aided extractions were 8.1, 43.6 and 44.0%, respectively. The collagens were generally colorless although collagens from the enzymes aided-extractions were slightly darker. Based on the e-nose evaluation, the collagens were considered odorless. The pH of all the collagens was in the vicinity of 3; however, those extracted with papain had significantly higher pH. The polypeptide profiles obtained in the SDS-PAGE analysis for pepsin extracted collagen were similar to those of acid solubilized collagens. Papain extracted collagen had distinctly different SDS-PAGE pattern. All the extracted collagens were of type 1 with apparent peptides molecular weight distribution of 37 to 250 kDalton. They had high solubility in pH 2 to 5 and increasing NaCl concentration up to 6%.